The Greatest Animal in the Jungle - Martins, Sope (Nigeria, 2018)
On Afuwe's birthday, his godfather, Tortoise, gives him a gift that grants him five wishes. Afuwe's ultimate wish is to become the greatest animal in the jungle instead of the mouse that he is...
Keywords: Animal Adventure; Juvenile Fiction